Comparison of biology of tea mosquito bug, Helopeltis bradyi Waterhouse (Hemiptera: Miridae) on different phenological stages of cocoa (Theobroma cacao L.) - Alagar, M.; Bhat, Keshava (Journal of Plantation Crops, 2017)
Among the insect pests recorded on cocoa, tea mosquito bug, Helopeltis spp. is a predominant one. Three species of tea mosquito bug viz., Helopeltis antonii, H. bradyi and H. theivora causes damage to cocoa. Among them, H. bradyi is a predominant species feeding on cocoa. Different phenological stages of cocoa viz., tender shoots, cherelles and pods were compared for fecundity, nymphal development, survival and adult longevity of H. bradyi. The fecundity, nymphal emergence and egg hatchability was highest in cocoa pods and lowest in cherelles. Highest numbers of eggs were recorded in tender shoot (110.5 numbers) followed by pods (107.5). Significantly lower number of eggs were recorded in cherelles (103.3 numbers). The total number of nymphs emerged and egg hatchability were significantly highest in tender shoots. The nymphs developed much earlier on pods than on tender shoots and cherelles. The total nymphal developmental period of H. bradyi was higher on tender shoot (224.5 h) followed by cherelles (218.3 h) and was lowest on pods (202.7 h). The adult survival was the highest (98.6%) when fed on cocoa pods compared to that of cherelles. Both females (31.5 days) and males (29.8 days) lived longest on pods than on cherelles. Whereas, in tender shoots both the male and female recorded significantly the lowest adult longevity of 21.3 days and 23.2 days, respectively. Tender shoots were found to be an inferior food source for adults than cherelles and pods. It is revealed that the availability of pods is critical for the fecundity, development, survival and longevity of H. bradyi.